PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) (Studi Di Kantor Kecamatan Aur Birugo Tigo Baleh Kota Bukittinggi) - Handrina, Emi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Services can basically be defined as the activity of a person or organization, either directly or indirectly to meet the needs. Services can be divided into services, goods and administrative services. Quality public services not only refers to the ministry alone, also emphasizes the process of conducting or distributing the service itself up into the hands of consumers. The purpose of this study was to determine how the implementation of the integrated administrative service districts (Patents) (studies at the District Office Eas Aur Birugo Tigo Baleh Kota Bukittinggi). This type of research that used in this research is descriptive using a quantitative approach to a study of an independent variable that is without compare or combine with other variables. Total population in this study of 750 people with an error rate of 10% (0.1), then the results can be obtained a sample of 88, calculated based on the formula Slovin. Techniques and tools of data collection using questionnaires and observation. Data analysis technique used in this study using quantitative descriptive technique using a Likert scale as a measuring tool in giving a score on each indicator measurement. The results based on the answers of the respondents indicate that there are no serious obstacles that can Patent implementation process at the District Office East Aur Birugo Tigo Baleh. Based on the results of this study can be used as a reference for the Eastern District office Aur Birugo Tigo Baleh can better support the creation of a vision and mission that has been made by the District Office East Aur Birugo Tigo Baleh (ABTB) Kota Bukittinggi.